COMPARACIÓN CLÍNICA Y RADIOGRÁFICA DE PULPOTOMÍAS REALIZADAS CON ELECTROCAUTERIO Y FORMOCRESOL EN MOLARES DECIDUOS: ESTUDIO PRELIMINAR (2018)
Purpose: The aim of this study was to compare the effect of electrosurgery to that of formocresol as pulp dressing agents in pulpotomized primary molars with carious pulp exposure.Material and methods: Twenty-eight primary molars of 17 children were treated pulpotomy technique. The teeth were randomly assigned to the electrosurgery (group 1, experimental) and formocresol (group 2, control). All teeth were treated with rubber dam. After removing tooth decay, pulp chamber was reached. The pulp stumps were touched with the electrode in mode three in the group 1. In the group 2, formocresol was placed with a cotton pellet over the pulp stumps for 5 minutes and removed; the pulp stumps were then covered by zinc oxide – eugenol paste. The teeth of both groups were restored with stainless steel crowns. The follow – up evaluation ranged from 8 to 30 days.Results: A clinical success (absence of mobility and fistulae) was obtained in 100% of both groups. Radiographically, 100% success was obtained in group one while in group the success decreased to 83.4%.Conclusions: The results were not statistically significant. However, the electrosurgery could be a good alternative for pulpotomy technique in primary molars.